Computational analysis of Cyclin D1 gene SNPs and association with breast cancer. Issue 1 (29th January 2021) - Aftab, Ayesha; Khan, Ranjha; Shah, Wasim; Azhar, Muhammad; Unar, Ahsanullah; Jafar Hussain, Hafiz Muhammad; Waqas, Ahmed
Abstract: CCND1 encodes for Cyclin D1 protein and single-nucleotide polymorphisms (SNPs) can modulate its activity. In the present study, the impact of CCND1 SNPs on structure and/or function of Cyclin D1 protein using in silico tools was investigated. Our analysis revealed only one splice site SNP (c.1988+5G<A) can effect CCND1 function. Subsequently, 78 out of 169 missense variants were predicted as pathogenic by Polyphen2, SIFT, PROVEAN, SNPs&GO, and PANTHER, and 4/78 missense SNPs were further evaluated because these four SNPs were found to be reside in highly conserved region of Cyclin D1. However, they did not show any major impact on tertiary structure and domain of Cyclin D1 but overall R15S and A190S has displayed a significant diseased phenotype and an altered molecular mechanism predicted by MutPred, FATHMM, SNPeffect, SNAP2, and PredictSNP. Consistently, A190S, R179L, and R15S may also cause a decrease in stability of Cyclin D1 anticipated by I-Mutant, HOPE and SNP effect. Furthermore, the Kaplan–Meier plotter has explained that high expression of CCND1 is associated with less survival rate of breast cancer patients. Altogether our study suggests that c.1988+5G<A, R15S, R179L, and A190S SNPs could directly or indirectly destabilize Cyclin D1.